Composite lead-free solder for brazing

By adding micron-level X metal powder to the Sn-Bi-X low-temperature solder paste to form Sn-Bi-X intermetallic compounds, the problems of dendrites segregation and coarse structure in low-temperature solder were solved, and the problems of dendrites segregation and coarse structure of Sn-Bi-based alloy solder were significantly improved. Improves the mechanical properties and reliability of solder joints.

CN119387946APending Publication Date: 2025-02-07SHANGHAI TECHN INST OF ELECTRONICS & INFORMATION
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411660530.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing Sn-Bi alloy solder is prone to dendrite segregation and thickening of structure in low-temperature welding, resulting in poor reliability and mechanical properties of the solder joints and high cost.

Method used

The composite lead-free solder is made by adding X-metal powder with a particle size of 0.5 μm to 10 μm to the Sn-Bi low-temperature solder paste, such as spherical copper powder, silver powder or nickel powder, and mechanically stirring. When brazing is performed in the preset temperature range, Sn-Bi-X intermetallic compound is formed.

Benefits of technology

It significantly reduces Bi segregation, prevents the occurrence of dendrites, improves the mechanical properties and reliability of the solder joints, including the improvement of shear strength and tensile strength, and is at a lower cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387946A_ABST
    Figure CN119387946A_ABST
Patent Text Reader

Abstract

The invention provides a composite lead-free solder for brazing. The composite lead-free solder comprises the following components: Sn-Bi series low-temperature solder paste; the particle size of the X metal powder is between 0.5 mu m and 10 mu m; the composite lead-free solder is prepared by mechanically stirring the Sn-Bi series low-temperature solder paste and the X metal powder at the normal temperature, and the mass ratio of the Sn-Bi series alloy solder paste to the X metal powder ranges from 10: 1 to 30: 1; and when brazing is carried out in a preset temperature interval, the composite lead-free solder forms a Sn-Bi-X intermetallic compound. The micron-sized X metal powder is added into the Sn-Bi system low-temperature solder paste in a mechanical stirring mode, and the preparation method is simple and efficient; due to the formation of the Sn-Bi-X intermetallic compound, Bi segregation is remarkably reduced, and dendritic segregation is prevented; the selection of the superimposed components, the control of the combined mass ratio and the welding reliability of the sintered joint are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic welding materials, in particular to a composite lead-free solder for brazing. Background Art

[0002] With the rapid development of electronic technology, short, light and thin electronic products have become a selling point. New chips usually cannot withstand the high temperature of welding, especially the problem of solder joint defects caused by high temperature when welding BGA components is becoming more and more prominent, so low-temperature welding has become a trend. Because lead can harm human health and the ecological environment, many countries have laws restricting the use of traditional Sn-Pb solder. Therefore, it is urgent to develop an economical, non-toxic, environmentally friendly, low-temperature sintered lead-free solder as a substitute.

[0003] The lead-free low-temperature soldering materials used in the field of low-temperature soldering in the prior art mainly include Sn-Bi alloys, Sn-Zn alloys, Sn-In alloys and other system solders. Due to the scarcity and high price of the indium (In) element, this alloy solder cannot be promoted for use. The problem of easy oxidation of metallic zinc (Zn) limits the application scenarios of Sn-Zn alloy solders. Sn-Bi alloy solders are prone to dendrite segregation and structural coarsening during the solidification process due to their large melting range. In addition, stress imbalance leads to solder joint peeling, which seriously affects the reliability of the solder joints.

[0004] In order to improve the reliability of solder joints after brazing with Sn-Bi alloy solder, most of the existing technologies use microalloying methods to improve it. That is, a trace amount of Ni, Cu, Ag, Zn, Sb and other metals are added to the Sn-Bi alloy and melted at high temperature to form a whole, and then cooled to form solder. In the solder, intermetallic compounds can be formed with metal Sn, which refines the grains and slows down the formation of Bi-rich layers. Since dendritic Sn-Bi eutectics still exist in the crystallization after Sn-Bi microalloying, it can only improve the local welding performance, but cannot significantly improve its comprehensive performance. Moreover, as the aging progresses, the Sn in the Sn-Bi eutectic structure will continue to diffuse to the copper substrate, resulting in a reduction in the Sn content in the Sn-Bi eutectic structure, and the growth of the Bi-rich layer cannot be avoided, which has limited improvement on the reliability of the solder joints.

[0005] Therefore, there is an urgent need for a composite lead-free solder for brazing that has a simple processing method, suppressed segregation of the Bi-rich layer, significantly improved mechanical properties of the solder joint, good antioxidant properties, and low cost. Summary of the invention

[0006] In order to solve the problem that the above-mentioned background technology cannot cost-effectively solve the problem that Sn-Bi alloy solder is prone to dendrite segregation, the present invention provides the following technical solution:

[0007] A composite lead-free solder for brazing, comprising the following components:

[0008] Sn-Bi low temperature solder paste;

[0009] X metal powder, particle size between 0.5μm-10μm;

[0010] The composite lead-free solder is made by mechanically stirring the Sn-Bi low-temperature solder paste and the X metal powder at room temperature, wherein the mass ratio of the Sn-Bi alloy solder paste to the X metal powder is in the range of 10:1 or more and 30:1 or less;

[0011] When soldering is performed in a preset temperature range, the composite lead-free solder forms a Sn-Bi-X intermetallic compound, and the preset temperature range is 180 degrees to 240 degrees.

[0012] The technical effect of the technical solution is that, in order to improve the welding reliability of the Sn-Bi solder sintered joint, the micron-level X metal powder is added into the Sn-Bi low-temperature solder paste by mechanical stirring, and the preparation method is simple and efficient; the Sn-Bi low-temperature solder paste contains a large amount of Bi, and Bi and Sn undergo limited solid solution, and the supersaturated Bi is easy to exist alone outside the matrix to form a brittle phase, which will lead to increased solder brittleness, while the formation of the Sn-Bi-X intermetallic compound significantly reduces the Bi segregation and prevents the occurrence of dendrite segregation; the selection of the superimposed components and the control of the combined mass ratio significantly improve the welding reliability of the sintered joint.

[0013] Preferably, after brazing is completed in a preset temperature range, there are metal particles left by the X metal powder that has not been completely melted; and the metal particles are sandwiched between the formed Sn-Bi-X intermetallic compound. In the manufacturing process of electronic products, common substrate materials include Cu plates, etc., which react with Sn and corresponding metal elements at the interface to form intermetallic compounds (IMC). During the welding process, the IMC generated by chemical reactions of two or more metal elements in contact with each other at a clean interface nucleates and grows here until it is finally cooled and crystallized, forming a strong chemical bond connecting the substrate and the device pins. In this technical solution, the micron metal particles added to the solder paste are not completely melted after welding, and a part of them is sandwiched between the metal alloy after welding as metal micron particles, forming a partition effect.

[0014] Preferably, the Sn-Bi low-temperature solder paste is Sn42Bi58;

[0015] Or Sn-58Bi-Y alloy, wherein Y is one of Zn, Ag, and Ni.

[0016] Preferably, the mechanical stirring at room temperature is made as follows:

[0017] The Sn-Bi alloy solder paste and the X metal powder are placed in a high-speed mixer and stirred at a speed of 2500 r / min-4000 r / min for 10 min-20 min.

[0018] Preferably, the X metal powder is spherical copper powder of 1 to 3 μm, the mass ratio of the Sn-Bi alloy solder paste to the X metal powder is in a range of 10:1 or more and 20:1 or less; and the purity of the X metal powder is 99.99%.

[0019] Preferably, the melting temperature of the solder is measured by a differential scanning calorimeter, and there is an obvious endothermic peak below 180°C.

[0020] Preferably, the X metal powder is spherical nickel powder of 1 to 3 μm, the mass ratio of the Sn-Bi alloy solder paste to the X metal powder is greater than 10:1 and less than 20:1; and the purity of the X metal powder is greater than 99%.

[0021] Preferably, the X metal powder is spherical silver powder of 1 to 7 μm; the mass ratio of the Sn-Bi alloy solder paste to the X metal powder is greater than 10:1 and less than 15:1; and the purity of the X metal powder is greater than 99%.

[0022] Preferably, the X metal powder is spherical silver powder with a diameter of 1 to 5 μm, the mass ratio of the Sn-Bi alloy solder paste to the X metal powder is in the range of 10:1, and the purity of the X metal powder is 99.99%.

[0023] Preferably, the mechanical stirring at room temperature is made as follows:

[0024] The Sn-Bi alloy solder paste and the X metal powder were placed in a high-speed mixer and stirred at a speed of 3000 r / min for 10 min.

[0025] The beneficial effects of the present invention are as follows: the formation of Sn-Bi-X intermetallic compounds significantly reduces Bi segregation; the micron metal particles added to the solder paste are not completely melted after welding, and a part of them is sandwiched in the middle of the metal alloy after welding in the form of metal micron particles, forming a partition effect; the selection of superimposed components, the control of the combined mass ratio, the dispersion formation of Sn-Bi-X intermetallic compounds, and the dispersion of X metal micron particles in the middle of the metal alloy; through testing, it is found that the welding reliability of the sintered joint is significantly improved, and the mechanical properties of the joint, including shear strength and tensile strength, are significantly improved. Therefore, by adding an appropriate amount of micron metal particles to adjust the Young's modulus of the interconnection layer, a high-quality sintered joint is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0027] Figure 1a This is the melting characteristic curve of the Sn-Bi composite lead-free solder in the comparative example of the present invention.

[0028] Figure 1b This is the melting characteristic curve of the Sn-Bi-Ag composite lead-free solder in Example 1 of the present invention.

[0029] Figure 1c This is the melting characteristic curve of the Sn-Bi-Cu composite lead-free solder in Example 2 of the present invention.

[0030] Figure 1d The melting characteristic curve of the Sn-Bi-Ni composite lead-free solder in Example 3 of the present invention is

[0031] Figure 2 The spreading performance and wetting performance of Examples 1 to 3 and Comparative Example 1 are compared.

[0032] Figure 3a The following is a comparison of the spreading ratios of Examples 1 to 3 and Comparative Example 1.

[0033] Figure 3b The wetting angles of Examples 1 to 3 and Comparative Example 1 are compared.

[0034] Figure 4a The microstructure of the Sn-Bi composite lead-free solder after soldering in the comparative example of the present invention.

[0035] Figure 4b The microstructure of the Sn-Bi-Ag composite lead-free solder after soldering in Example 1 of the present invention.

[0036] Figure 4c The microstructure of the Sn-Bi-Cu composite lead-free solder after soldering in Example 2 of the present invention.

[0037] Figure 4d The microstructure of the Sn-Bi-Ni composite lead-free solder after soldering in Example 3 of the present invention.

[0038] Figure 5a This is the microstructure of the interface IMC layer of the Sn-Bi composite lead-free solder after soldering in the comparative example of the present invention.

[0039] Figure 5b This is the microstructure of the interface IMC layer of the Sn-Bi-Ag composite lead-free solder after soldering in Example 1 of the present invention.

[0040] Figure 5c This is the microstructure of the interface IMC layer after soldering of the Sn-Bi-Cu composite lead-free solder in Example 2 of the present invention.

[0041] Figure 5d This is the microstructure of the interface IMC layer after soldering of the Sn-Bi-Ni composite lead-free solder in Example 3 of the present invention.

[0042] Figure 6a The tensile strength comparison of Examples 1 to 3 and Comparative Example 1 is shown.

[0043] Figure 6b The elongation comparison of Examples 1 to 3 and Comparative Example 1 is shown.

[0044] Figure 6c The shear strength comparison of Examples 1 to 3 and Comparative Example 1 is shown. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] A composite lead-free solder for brazing, comprising the following components:

[0047] Sn-Bi low temperature solder paste;

[0048] X metal powder, particle size between 0.5μm-10μm;

[0049] The composite lead-free solder is prepared by mechanically stirring Sn-Bi low-temperature solder paste and X metal powder at room temperature, wherein the mass ratio of Sn-Bi alloy solder paste to X metal powder is in the range of 10:1 or more and 30:1 or less;

[0050] When soldering is performed in a preset temperature range, the composite lead-free solder forms a Sn-Bi-X intermetallic compound, and the preset temperature range is 180 degrees to 240 degrees.

[0051] The micron-sized X metal powder is added into the Sn-Bi low-temperature solder paste by mechanical stirring, and the preparation method is simple and efficient; the Sn-Bi low-temperature solder paste contains a large amount of Bi, and Bi and Sn undergo limited solid solution. The supersaturated Bi is easy to exist alone outside the matrix to form a brittle phase, which will increase the brittleness of the solder, while the formation of the Sn-Bi-X intermetallic compound significantly reduces the Bi segregation and prevents the occurrence of dendrite segregation; the selection of the superimposed components and the control of the combined mass ratio significantly improve the welding reliability of the sintered joint.

[0052] In some embodiments, after brazing is completed in a preset temperature range, there are metal particles left by the X metal powder that has not been completely melted; and the metal particles are sandwiched between the formed Sn-Bi-X intermetallic compound. In the manufacturing process of electronic products, common substrate materials include Cu plates, etc., which react with Sn and corresponding metal elements at the interface to form intermetallic compounds (IMC). During the welding process, the IMC generated by chemical reactions of two or more metal elements in contact with each other at a clean interface nucleates and grows here until finally cooling and crystallizing, forming a strong chemical bond connecting the substrate and the device pins. Because the micron metal particles added to the solder paste are not completely melted after welding, a part of the metal micron particles are sandwiched between the metal alloy after welding, forming a partition effect.

[0053] In some embodiments, the Sn-Bi low temperature solder paste is Sn42Bi58;

[0054] Or Sn-58Bi-Y alloy, wherein Y is one of Zn, Ag, and Ni.

[0055] In some embodiments, mechanical stirring at room temperature is made into:

[0056] Put the Sn-Bi alloy solder paste and X metal powder into a high-speed mixer and stir them at a speed of 2500r / min-4000r / min for 10min-20min.

[0057] In some embodiments, the X metal powder is spherical copper powder with a diameter of 1 to 3 μm, the mass ratio of the Sn-Bi alloy solder paste to the X metal powder is greater than 10:1 and less than 20:1, and the purity of the X metal powder is 99.99%.

[0058] In some embodiments, the melting temperature of the solder is measured by differential scanning calorimetry and has an obvious endothermic peak below 180°C.

[0059] In some embodiments, the X metal powder is spherical nickel powder of 1-3 μm, the mass ratio of Sn-Bi alloy solder paste to the X metal powder is greater than 10:1 and less than 20:1; and the purity of the X metal powder is greater than 99%.

[0060] In some embodiments, the X metal powder is spherical silver powder with a diameter of 1 to 7 μm; the mass ratio of the Sn-Bi alloy solder paste to the X metal powder is greater than 10:1 and less than 15:1; and the purity of the X metal powder is greater than 99%.

[0061] In some embodiments, the X metal powder is spherical silver powder with a diameter of 1 to 5 μm, the mass ratio of the Sn-Bi alloy solder paste to the X metal powder is in the range of 10:1, and the purity of the X metal powder is 99.99%.

[0062] In some embodiments, mechanical stirring at room temperature is made into:

[0063] Sn-Bi alloy solder paste with a mass ratio of 10:1 and 1-5 μm spherical silver powder were put into a high-speed mixer and stirred at a speed of 3000 r / min for 10 minutes.

[0064] Specifically, first weigh 100 g of lead-free solder paste (Sn42Bi58), then weigh 10 g of spherical silver powder, mix them manually, then put the sample into a high-speed mixer (3000 r / min) and stir for 10 min, then pour it out and set aside.

[0065] Then, it is brazed with the copper substrate at about 200°C to obtain an interface IMC layer, as shown in Figure 4. The microstructure of the interface IMC layer after brazing is observed. The cross-sectional morphology of the Sn-Bi-Ag solder joint interface IMC layer is very dense and flat. The IMC grains at the Sn-Bi-Ag / copper substrate interface are small and evenly distributed. There are metal particles left by the X metal powder that has not been completely melted, and the metal particles are sandwiched between the formed Sn-Bi-X intermetallic compounds, and there is basically no Bi segregation phenomenon. The shear strength is tested, the shear strength is as high as 7.46MPa, the tensile strength is as high as 91.71MPa, and the welding reliability is the best.

[0066] Example 1

[0067] (1) First weigh 100g of lead-free solder paste (Sn42Bi58), then weigh 10g of spherical silver powder. Mix them manually first, then put the sample into a high-speed mixer (3000r / min) and stir for 10min, then pour it out and set aside.

[0068] (2) The melting temperature, spreadability and wetting angle of the solder were tested respectively. The microstructure inside and at the interface of the solder after brazing; the shear strength and ductility of the solder joint were tested. The test methods are as follows: the melting temperature of the solder was measured by a DSC214 differential scanning calorimeter, the protective atmosphere was nitrogen, the temperature range was 40-400℃, and the heating rate was 5℃ / min; the microstructure was observed by a SEM5000 scanning electron microscope; the mechanical properties of the solder were tested by a WDW-2D microcomputer-controlled electronic universal testing machine; GB / T 11363-2008 was used as the reference standard for the shear strength test of the solder joint, and GB / T228.1-2021 was used as the reference standard for the tensile test of the solder. The spreadability of the solder was tested by a SX2-5-12A box-type resistance furnace, and GB / T 11364-2008 was used as the reference standard for the spreading rate test. The wetting angle was tested by an optical contact angle tensiometer.

[0069] Example 2

[0070] (1) First weigh 100g of lead-free solder paste (Sn42Bi58), then weigh 10g of spherical copper powder. Mix them manually first, then put the sample into a high-speed mixer (3000r / min) and stir for 10min, then pour it out and set aside.

[0071] (2) The melting temperature, spreading property and wetting angle of the solder were tested respectively. The microstructure inside and at the interface of the solder after brazing, and the shear strength and ductility of the brazing point were tested. The test method was the same as that of Example 1.

[0072] Example 3

[0073] (1) First weigh 100g of lead-free solder paste (Sn42Bi58), then weigh 10g of spherical nickel powder. Mix manually, then put the sample into a high-speed mixer (3000r / min) and stir for 10min, then pour it out and set aside.

[0074] (2) The melting temperature, spreading property and wetting angle of the solder were tested respectively. The microstructure inside and at the interface of the solder after brazing, and the shear strength and ductility of the brazing point were tested. The test method was the same as that of Example 1.

[0075] Comparative Example 1

[0076] (1) First, weigh 100 g of lead-free solder paste (Sn42Bi58) as a sample, then put the sample into a high-speed blender (3000 r / min) and stir for 10 min, then pour it out and set aside.

[0077] (2) The melting temperature, spreading property and wetting angle of the solder were tested respectively. The microstructure inside and at the interface of the solder after brazing, and the shear strength and ductility of the brazing point were tested. The test method was the same as that of Example 1.

[0078] For welding materials, melting characteristics are an important aspect of the material's welding performance. Figure 1a It can be seen that the melting temperature of the Sn-Bi eutectic solder alloy is 143°C, and its melting characteristic curve presents a standard single peak shape, which is caused by the melting of the Sn-Bi alloy. Figure 1b The melting temperature of Sn-Bi-Ag is 240.3℃, and there is an obvious endothermic peak at 136.4℃, but the amount is less than that of Sn-Bi, which means that the Ag powder melts directly during the heating process and then mixes with the Sn-Bi alloy. Figure 1c The melting range of Sn-Bi-Cu is 265.9~270.7℃. Figure 1d The melting range of Sn-Bi-Ni is 265.8~268.5℃, and there is an inconspicuous endothermic peak at 137.5℃, which indicates that the copper powder and nickel powder are not melted separately, but diffused into the liquid alloy in a dissolved manner.

[0079] Good wettability can be understood as the ability of the solder paste to spread on the surface of the pad after melting and to form a metallurgical connection with the pad to generate a specific intermetallic compound. The way to judge wettability is to observe the wetting angle formed between the solder paste and the pad. Generally, the angle between the solder paste and the pad is greater than 90°, which is defined as poor wettability, that is, large surface tension, and vice versa. Spreading rate refers to the flow and distribution ability of molten solder on the surface of the metal to be welded; solder with good spreading can evenly cover the surface to be welded to form a uniform and continuous solder joint. Both wettability and spreading directly affect the formation and quality of solder joints. Wettability is usually measured by contact angle, while spreading considers more the fluidity and coverage of solder. It must be noted that the wetting state needs to be combined with the actual welding scene / conditions. Too poor wettability will lead to low bonding ability between solder and pad, resulting in low solder joint strength, poor solder joint size, irregular shape, multiple solder beads and other problems. Excessive wettability is also undesirable. Solder with too high wettability is likely to cause insufficient solder joint height after molten soldering, and it is easy to cause solder out of bounds. The test results of the spreading rate are as follows: Figure 2 , Figure 3a and Figure 3b As shown in the figure, with the addition of doped metal powder, the overall spreading rate of the solder alloy on the copper plate is Sn-Bi-X (standard sample>Ag>Ni>Cu) showing a downward trend. Figure 3bThis is a test of the wetting angle. It was observed that the wetting angle of the doped copper powder was the smallest, at 20.37°, indicating that the wettability of the doped copper powder was better than that of the standard sample before modification. This makes the alloy and the copper substrate more closely bonded, and the problem of solder falling off is less likely to occur. In addition, the wetting angles of the doped silver powder and the doped nickel powder are also less than 90°, which is also within an acceptable range.

[0080] Figure 4a-4d The SEM images of Sn-Bi and Sn-Bi-X (X = Ni / Ag / Cu) solders after sintering are shown. Figure 4a As shown, the microstructure of Sn-Bi alloy is a typical eutectic structure composed of white Bi-rich phase and dark Sn phase. The white structure in the figure is the Bi-rich area, which is a bismuth-based solid solution composed of Bi and a small amount of Sn. The black structure is the Sn-rich area, which is a Sn-based solid solution composed of Sn and a small amount of Bi. The solder contains a large amount of Bi, and Bi and Sn undergo limited solid solution. The supersaturated Bi is easy to exist alone outside the matrix to form a brittle phase, which will increase the brittleness of the solder. It can be seen that the Bi segregation in Sn-Bi is very serious. Compared with Sn-Bi, Figure 4b , Figure 4c , Figure 4d The Bi segregation phenomenon is significantly improved. Figure 4b Sn-Bi-Ag has obvious spherical silver powder particles, fine and uniform structure, and basically no segregation phenomenon; Figure 4c In the Sn-Bi-Cu structure, Bi is not connected into a network, and granular Bi is precipitated. In addition, there are many fine Bi precipitations on the primary Sn matrix, which means that the addition of alloy elements has an inhibitory effect on the formation of coarse flake Bi. Figure 4d The Sn-Bi-Ni structure shows a coarse microstructure, but white segregation is suppressed.

[0081] In the manufacturing process of electronic products, common substrate materials such as Cu plates will react with Sn and corresponding metal elements at the interface to form intermetallic compounds (IMC). During the welding process, two or more metal elements in contact with each other at the clean interface generate IMCs through chemical reactions, which nucleate and grow here until they are finally cooled and crystallized, forming strong chemical bonds connecting the substrate and the device pins. For high-quality brazing joints, a thin, continuous, and uniform IMC layer is crucial.

[0082] from Figure 5a-5d It can be seen that Figure 5a Sn-Bi, Figure 5b The cross-sectional morphology of the IMC layer at the Sn-Bi-Ag solder joint interface is very dense and smooth. Figure 5c The Sn-Bi-Cu solder joint interface is slightly uneven. Figure 5dThe cross-sectional morphology of the IMC layer at the solder joint interface of Sn-Bi-Ni shows obvious cracks and is uneven. It can be inferred that the IMC grains at the interface of Sn-Bi / copper substrate and Sn-Bi-Ag / copper substrate are small, thin and evenly distributed. The IMC grain size and thickness in the Sn-Bi-Cu / copper substrate have increased. The main reason for this phenomenon is that the addition of Cu powder increases the Cu content in the solder. During the welding process, copper atoms dissolve in the liquid solder and move with the internal movement of the solder. This phenomenon leads to an increase in the concentration of Cu atoms at the welding interface, which in turn promotes the growth of IMC. The number and thickness of IMC grains in the Sn-Bi-Ni / copper substrate are significantly reduced.

[0083] The tensile strength and elongation of solder are important indicators for evaluating soldering quality. Figure 6a-6b As shown in the figure, the fracture of the Sn-Bi / copper substrate welding joint is plastic fracture, so the elongation is as high as 17.33%. After adding silver powder and copper powder to the Sn-Bi solder, the amount of fine IMC dispersed in the solder increases, which has a strengthening effect on the solder, increasing the tensile strength of the solder alloy while the plastic fracture gradually changes to brittle fracture. Since the addition of nickel powder will form brittle and hard heterogeneous metal compounds, the metal compounds are dispersed in the matrix and can strengthen the solder alloy. Therefore, with the addition of nickel powder, the hardness of the alloy gradually increases. The tensile strength of the joint is as high as 93.59MPa. Due to the formation of a large number of holes at the joint, the elongation drops to 9.67%, which is basically a brittle fracture.

[0084] The shear strength of the weld joint refers to the maximum shear force that the weld joint withstands when it breaks under the force applied perpendicular to the weld joint surface. With the addition of silver, copper, and nickel metal powders, such as Figure 6c As shown in the figure, the shear strength of the weld joint increases from 0.16MPa to 7.46MPa, 3.5MPa, and 5.17MPa, respectively. The welding reliability is significantly improved. This is because the alloy elements diffuse fully in the weld joint during the welding process, which inhibits the bismuth from existing alone outside the matrix due to supersaturation, forming a coarse flaky brittle phase. Among them, the grains in the intermediate diffusion transition layer formed by the Sn-Bi-Ag weld joint are small and uniform, with basically no segregation phenomenon, so the shear strength is as high as 7.46MPa, and the welding reliability is the best. The grain size of the structure in the intermediate diffusion transition layer of the Sn-Bi-Cu / Ni weld joint is uneven, and there is a certain porosity, so the shear strength is slightly lower.

[0085] Specifically, the shear strength of the Sn-Bi-Ag weld joint increased to 7.46MPa, and the tensile strength was as high as 91.71MPa; the shear strength of the Sn-Bi-Cu weld joint increased to 3.5MPa, and the tensile strength was as high as 86.67MPa; the shear strength of the Sn-Bi-Ni weld joint increased to 5.17MPa, and the tensile strength was as high as 93.59MPa.

[0086] The above embodiments show that through the implementation of the technical solution of the present invention, the phenomenon of dendrite segregation that is prone to occur during the solidification process of Sn-Bi alloy solder due to its large melting range is suppressed, and the mechanical properties of the welded joint are significantly improved. Overall, the comprehensive performance of the solder is greatly improved.

[0087] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite lead-free solder for brazing, characterized in that: Includes the following components: Sn-Bi low temperature solder paste; X metal powder, particle size between 0.5μm-10μm; The composite lead-free solder is made by mechanically stirring the Sn-Bi low-temperature solder paste and the X metal powder at room temperature, wherein the mass ratio of the Sn-Bi alloy solder paste to the X metal powder is in the range of 10:1 or more and 30:1 or less; When soldering is performed in a preset temperature range, the composite lead-free solder forms a Sn-Bi-X intermetallic compound, and the preset temperature range is 180 degrees to 240 degrees.

2. The composite lead-free solder according to claim 1, characterized in that: After brazing is completed in the preset temperature range, metal particles remain from the X metal powder that has not been completely melted; and the metal particles are sandwiched between the formed Sn-Bi-X intermetallic compound.

3. The composite lead-free solder according to claim 2, characterized in that: The Sn-Bi low temperature solder paste is Sn42Bi58; Or Sn-58Bi-Y alloy, wherein Y is one of Zn, Ag, and Ni.

4. The composite lead-free solder according to claim 3, characterized in that: The mechanical stirring at room temperature is made by: The Sn-Bi alloy solder paste and the X metal powder are placed in a high-speed mixer and stirred at a speed of 2500 r / min-4000 r / min for 10 min-20 min.

5. The composite lead-free solder according to claim 3, characterized in that: The X metal powder is spherical copper powder with a diameter of 1 to 3 μm. The mass ratio of the Sn-Bi alloy solder paste to the X metal powder is greater than 10:1 and less than 20:

1. The purity of the X metal powder is 99.99%.

6. The composite lead-free solder according to claim 3, characterized in that: The melting temperature of the solder was measured by differential scanning calorimetry, and there was an obvious endothermic peak below 180°C.

7. The composite lead-free solder according to claim 6, characterized in that: The X metal powder is spherical nickel powder with a diameter of 1 to 3 μm. The mass ratio of the Sn-Bi alloy solder paste to the X metal powder is greater than 10:1 and less than 20:

1. The purity of the X metal powder is greater than 99%.

8. The composite lead-free solder according to claim 6, characterized in that: The X metal powder is spherical silver powder with a diameter of 1 to 7 μm; the mass ratio of the Sn-Bi alloy solder paste to the X metal powder is greater than 10:1 and less than 15:1; and the purity of the X metal powder is greater than 99%.

9. The composite lead-free solder according to claim 8, characterized in that: The X metal powder is spherical silver powder with a diameter of 1 to 5 μm, the mass ratio of the Sn-Bi alloy solder paste to the X metal powder is 10:1, and the purity of the X metal powder is 99.99%.

10. The composite lead-free solder according to claim 9, characterized in that: The mechanical stirring at room temperature is made into: The Sn-Bi alloy solder paste and the X metal powder were placed in a high-speed mixer and stirred at a speed of 3000 r / min for 10 min.

Citation Information

Cited By

  • High-reliability low-temperature Sn-Bi-based lead-free solder alloy

    CN119857962A